OPTIMASI FORMULA SALEP EKSTRAK ETANOL 96% HERBA LAMPASAU (DIPLAZIUM ESCULENTUM SWARTZ.) MENGGUNAKAN VARIAN BASIS SALEP - Aristha Novyra Putri; Ridhati Afriani Abdi; Dyera Forestryana (Sekolah Tinggi Ilmu Kesehatan Borneo Lestari Banjarbaru, 2019)
ABSTRACT Herba Lampasau (Diplazium esculentum Swartz.) contains of flavonoids, saponins and tannins which act as antibacterial, antiseptic, and astringent in wound healing with 20% concentration, to facilitate its use it is formulated in the form of ointment. This study aimed to determine the optimum ointment formula based on before and after of Borneo Journal of Phamascientech, Vol. 03, No. 02, Oktober Tahun 2019 ISSN-Print. 2541-3651 ISSN-Online. 2548 – 3897 Research Article 179 the freeze thaw stability test of its physical characteristics and stability with variations of hydrocarbon base, absorption, washed water, and water soluble. Ointment preparations were made by smelting method, data analysis method on organoleptic, homogeneity and viscosity descriptively while in pH test, spreadability and statistical adhesion of one-way ANOVA. The results showed that the whole formula was semisolida, blackish green, distinctive smelling, homogeneous preparation but after the freeze thaw stability test it was not homogeneous anymore, preparation pH was 5.14- 6.63, preparation spread was 0-66.27 g.cm2 / s, power sticks <1 second, and viscosity 8840-19380 cP. Statistically the value (p-value > 0,05) showed that was not significant before and after the freeze thaw stability test, the overall formula was stable but at pH testing for formulas 2-4 there was a significant change in stability. Thus, it can be concluded that formula 1 on a hydrocarbon basis is the most optimal formula based on its physical characteristics and stability. Keywords: Lampasau; Ointment; Ointment base; Optimization; Optimal formula